Antibacterial Activity Test of Patchouli Leaf Essential Oil Facemist (Pogostemon cablin Benth) Against Cutibacterium acnes Bacteria - Rahayu, Sri; Mayasari, Ulfayani; Selvia, Irda Nila (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2025)
Cutibacterium acnes bacteria are gram-positive anaerobic bacteria that play a role in the pathogenesis of Acne vulgaris (acne). The use of facemist containing natural active ingredients of patchouli leaf essential oil (Pogostemon cablin Benth) can be an alternative in inhibiting the growth of acne-causing bacteria. This study aims to determine the antibacterial activity of patchouli leaf essential oil facemist (Pogostemon cablin Benth) against Cutibacterium acnes bacteria. The method used in making essential oils by steam distillation, chemical compound analysis using Gas Chromatography-Mass Pectrometry (GC-MS) and antibacterial activity testing using the disc diffusion method then formulated into a facemist product and characterized. The results of the study showed that patchouli leaf essential oil had met the standard requirements and contained several of the highest chemical compound components, namely Patchouli alcohol (15.71% and 10.16%), Delta-Guaiene (CAS) (7.14%), Azulene, 1,2,3,4,5,6,7,8-Octahydro-1 (6.48%), 2-Butynyl-5-Hydroxy-3-Oxo-4-Hexanoic Acid Delta-Lactone (5.89%) and 1,1,4,7-Tetramethyldecahydro-1H-Cyclopropa[E] Azulene-4-Ol (5.17%) and the presence of antibacterial activity against Cutibacterium acnes bacteria with concentrations of 10%, 20%, 30%, 40% and 50% with inhibition zone diameters of 11.18 mm, 17.66 mm, 22.36 mm, 23.10 mm and 24.76 mm and the diameter of the antibacterial facemist inhibition zone with concentrations of 20% and 30% obtained results of 20.93 mm and 23.76 mm, then the facemist preparation showed characterization that was in accordance with the product's standard requirements. Based on the test results, it is known that the antibacterial face mist made from patchouli leaf essential oil has the ability to inhibit Cutibacterium acnes bacteria.